The most effective and essential way of improving the oral health status education - S Chachra; P Dhawan; T Kaur; A K Sharma (Wolters Kluwer Medknow Publications, 2011)
Background: Oral health is an essential component of health throughout life. Two major oral diseases, dental caries and periodontal diseases, are both ancient and widespread. The oral health situation analysis demands that the preventive program be implemented in both the developing and developed countries. Therefore, this study was conducted to evaluate the effectiveness of delivering the primary preventive strategies through non dental and dental personnel. Aims and Objectives: To develops the preventive package for improving the oral health status of children utilizing the different communication approaches. To find out the most feasible and effective communication approach for delivering the preventive package. To evaluate the changes produced in terms of various soft and hard core parameters after 6 months of implementation of the oral-health preventive package in the school children of different study groups as compared to control. Materials and Methods: This study was conducted on total of 972 children in the age group of 5-16 years who were randomly selected from four schools of Chandigarh and Panchkula to evaluate and compare the prevalence of dental caries and knowledge, attitude, and practice about oral health. Results and Conclusions: The results of various parameters indicate that direct communication through the dentist proved to be the most effective communication approach as compared to the other two indirect communication approaches.